Critical Illness Factors Associated With Long-Term Mortality and Health Related Quality of Life Morbidity Following Community-Acquired Pediatric Septic Shock - Zimmerman, Jerry J (Crit Care Med, 2020)
OBJECTIVE: A companion article reports the trajectory of long-term mortality and significant health-related quality of life (HRQL) disability among children encountering septic shock. In this article, the investigators examine critical illness factors associated with these adverse outcomes. DESIGN: Prospective, cohort-outcome study, conducted 2013–2017. SETTING: Twelve United States academic pediatric intensive care units (PICUs). PATIENTS: Critically ill children, 1 month-18 years, with community-acquired septic shock requiring vasoactive-inotropic support. INTERVENTIONS: Illness severity, organ dysfunction, and resource utilization data were collected during PICU admission. Change from Baseline HRQL at the Month 3 follow-up was assessed by parent proxy-report employing the Pediatric Quality of Life Inventory or the Stein-Jessop Functional Status Scale. MEASUREMENTS AND MAIN RESULTS: In univariable modeling, critical illness variables associated with death and/or persistent, serious HRQL deterioration were candidates for multivariable modeling using Bayesian Information Criterion. The most clinically relevant multivariable models were selected among models with near optimal statistical fit. RESULTS: Three months following septic shock, 346/389 (88.9%) subjects were alive and 43/389 (11.1%) had died; 203/389 (52.2%) had completed paired HRQL surveys. Pediatric Risk of Mortality, cumulative Pediatric Logistic Organ Dysfunction (PELOD) scores, PICU and hospital durations of stay, maximum and cumulative vasoactive-inotropic scores, duration of mechanical ventilation, need for renal replacement therapy, extracorporeal life support or cardiopulmonary resuscitation, and appearance of pathologic neurological signs were associated with adverse outcomes in univariable models. In multivariable regression analysis (OR [95%CI]), summation of daily PELOD scores, 1.01/per point [1.01–1.02], p<0.001; highest vasoactive-inotropic score, 1.02/per point) [1.00–1.04], p=0.003; and any acute pathological neurologic sign/event, 5.04 [2.15–12.01], p<0.001 were independently associated with death or persistent, serious deterioration of HRQL at Month 3. CONCLUSIONS AND RELEVANCE: Biologically plausible factors related to sepsis-associated critical illness organ dysfunction and its treatment were associated with poor outcomes at Month 3 follow-up among children encountering septic shock.